Prevalence of multidrug-resistant hypervirulent Klebsiella pneumoniae without defined hypervirulent biomarkers in Anhui, China: a new dimension of hypervirulence - Ali, Md Roushan; Yang, Yu; Dai, Yuanyuan; Lu, Huaiwei; He, Zhien; Li, Yujie; Sun, Baolin (Frontiers in Microbiology, 2023)
Klebsiella pneumoniae (Kp) is an opportunistic pathogen that mainly causes nosocomial infections and hospital-associated pneumonia in elderly and immunocompromised people.However, multidrug-resistant hypervirulent Klebsiella pneumoniae (MDR-hvKp) has emerged recently as a serious threat to global health that can infect both immunocompromised and healthy individuals. Plasmid-mediated regulator of mucoid phenotype genes (rmpA and rmpA2) and other virulence factors (aerobactin and salmochelin) are mainly responsible for this phenotype. In this study, we collected 23 MDR-hvKp isolates and performed molecular typing, whole genome sequencing, comparative genomic analysis, and phenotypic experiments, including the Galleria mellonella infection model, to reveal its genetic and phenotypic features.Meanwhile, we discovered two MDR-hvKp isolates (22122315 and 22091569) that showed a wide range of hypervirulence and hypermucoviscosity without rmpA and rmpA2 and any virulence factors. In phenotypic experiments, isolate 22122315 showed the highest hypervirulence (infection model) with significant mucoviscosity, and conversely, isolate 22091569 exhibited the highest mucoviscosity (string test) with higher virulence compared to control. These two isolates carried carbapenemase (blaKPC−2), β-lactamase (blaOXA−1, blaTEM−1B), or extended-spectrum β-lactamase (ESBL) genes (blaCTX−M−15, blaSHV−106), outer membrane protein-coding genes (ompA), fimbriae encoding genes (ecpABCDER), and enterobactin coding genes (entAB, fepC). In addition, isolates 22122315 and 22091569 carried a novel mutation in locus FEBNDAKP_03184 (c. 2084A>C, p. Asn695Thr) and EOFMAFIB_02276 (c. 1930C>A, p. Pro644Thr), respectively, that led to putative tyrosine-protein kinase in capsule polysaccharide (cps) region. This study would be a strong theoretical reference and enhance the existing knowledge to identify and treat MDR-hvKp.